Pengaruh Lingkungan Kerja, Hubungan Kerja, Fasilitas Kerja, Kepuasan Kerja Dan Kompensasi Terhadap Kinerja Karyawan PT PLN (Persero) ULP Rayon Bandar Jaya - Bellaudi, Vinda Audhika; Suryadi, Suryadi (Jurnal Manajemen DIVERSIFIKASI, 2022)
EFFECT OF WORK ENVIRONMENT, WORK RELATIONSHIP, WORK FACILITIES, JOB SATISFACTION AND COMPENSATION ON THE PERFORMANCE OF PT PLN (PERSERO) ULP RAYON BANDAR JAYA EMPLOYEES of VINDA ADHIKA BELLAUDI NPM.17610089 Vinda Adhika Bellaudi Npm. 17610089. Effect of Work Environment, Work Relations, Work Facilities, Job Satisfaction and Compensation on Employee Performance of Pt Pln (Persero) Ulp Rayon Bandar Jaya. Supervisor (1) Ery Baskoro, S.E, M.M (2) Suryadi, S.E M.M One of the organizational resources that has an important role in achieving its goals is human resources, human resources have a major role in determining or developing an organization, therefore the progress of the organization is also determined by the quality and capabilities of human resources in it. The role of human resources is very important in a company, both private companies and government companies or state-owned enterprises. This study aims 1) to determine the effect of the work environment on employee performance. 2) to determine the effect of the employment relationship on employee performance. 3) to determine the effect of work facilities on employee performance. 4) to determine the effect of job satisfaction on employee performance. 5) to determine the effect of compensation on employee performance. 6) to determine the effect of the work environment, work relations, work facilities, job satisfaction and compensation on employee performance. In this study, the population was employees of PT PLN (Persero) ULP Rayon Bandar Jaya as many as 83 people. Data collection techniques using a questionnaire with a Likert scale. The results show that 1) there is a positive and significant influence between the work environment on employee performance 2) there is a positive and significant influence between the work relationship on employee performance. 3) there is a positive and significant influence between work facilities on employee performance 4) no there is a positive and significant influence between the influence of job satisfaction on employee performance 5) there is a positive and significant influence between work compensation on employee performance 6) there is a positive and significant influence between work environment, work relations, work facilities, job satisfaction and compensation on performance Employees. Keywords: Work Environment, Work Relations, Work Facilities, Job Satisfaction, Compensation and Employee Performance.